Evaluating the Implementation of Education Financing Policy: A Case Study of Elementary Schools in Brebes Regency - Rini Indriyani; Alfa Beti Rosita; Sutrisno Sutrisno (Journal of Educational Sciences, 2026)
Education financing plays a crucial role in ensuring equitable access and improving the quality of basic education services. This study aims to evaluate the implementation of education financing policy through the School Operational Assistance (BOS) program at the elementary school level in Brebes. The research employed a qualitative approach with an evaluative design to analyze four key dimensions: effectiveness, efficiency, transparency, and accountability. Data were collected through in-depth interviews, observations, and document analysis involving school principals, BOS treasurers, teachers, and school committee members. The findings reveal that the BOS program has contributed significantly to supporting school operations and learning activities. However, its implementation has not been fully optimal due to several constraints. The effectiveness of fund utilization is limited by planning practices that are not fully based on actual needs. Efficiency is affected by inappropriate spending priorities and delays in fund disbursement. Transparency has been initiated but remains inconsistent and lacks technological support. Meanwhile, accountability is largely administrative and has not been fully oriented toward performance evaluation. Overall, the implementation of education financing policy requires improvements in managerial capacity, monitoring systems, and technological integration to achieve more effective and sustainable outcomes.